How to keep well in wartime - Great Britain. Ministry of Health ; Central Council for Health Education (Great Britain); Clegg, Hugh Anthony, 1900- (London : His Majesty's Stationery Office, 1943)
1943 1943 1940s 28 pages : illustrations A WORD TO THOSE WHO WORRY and sympathy. Within this framework of security given him by the love of those around him the child needs as much freedom as is safe for him. Some parents like to encourage a child to feel dependent on them. If this goes too far the child may never quite grow out of this dependence. He will always be "tied to his mother's apron strings". So when you see your child (or your foster-child if you are one of the good samaritans who are caring for evacuees) taking a new and independent line of action that is not harmful, encourage him to go his own way, helping only when it is necessary. Remember, an unhappy child will probably also be an unhealthy child; conversely, without health a child will not be happy. There is one form of interference with a child's dignity that is still popular — this is corporal punishment, or, more commonly, "a good smack". A man skilled in the training of dogs has declared that a dog can be brought up by kindness and that there is no need to beat it. What good can you hope to achieve by physical punishment except obedience inspired by fear ? But a long moral lecture may be even more cruel than a quick slap. A Case for Patience and Tact. In the early days of this war, when children were being evacuated to all parts of the country, there was a big outcry because so many of them were found to wet their beds. Punishment did not do these children any good. They still went on wetting their beds. In some the cause may have been physical. In others the cause was psychological. In very early childhood the first thing a child, or infant, has to learn is to use the chamber. The mother teaches the infant this by putting it on the pot at regular intervals, and praising it when it uses it. Some children are quicker at learning this new trick than others. But there is really nothing to boast about in this. The child that is too perfect won't necessarily be happy. So a mother should not be worried or anxious because her child does not become "house-trained" all at once. In fact, if she does get worried and shows it, the child will probably go on wetting the bed and dirtying the napkin for a much longer time. A child should not be scolded or be told that he is dirty if he makes a mess when he is supposed not to — supposed not to, that is, according to the ideas of grown-up people. The child doesn't think in the same way as you do. Why should he ? Mother and Child. The mother has a very great responsibility, and bringing up and caring for a child call for endless patience. A child's future happiness is in its parents' hands, especially the mother's. No trouble should be too great, and the young mother has to realize that she must give up many of her personal pleasures and much of her freedom to devote to her children. But this is not to mean that a mother must always be interfering with her child, must always be 17 420/BS/7/16/18